EKSPLORASI PEMAHAMAN SISWA DALAM PEMBELAJARAN BANGUN DATAR SEGI EMPAT DI SD MENGGUNAKAN KONTEKS CAK INGKLING - Disnawati, Hermina; Indra Putri, Ratu Ilma; Hartono, Yusuf (PYTHAGORAS Jurnal Matematika dan Pendidikan Matematika, 2012)
Primary school curricullum lays the foundation of geometry knowledge; students learn geometry by exploring their environment. Many researchers found that students have difficulties in understanding quadrilaterals. Most of them assumed that quadrilateral is square. Therefore, the aim of this research is to develop activities that support students to know the different types and forms of quadrilaterals. A teacher and thirty nine of fifth grade students were invole in this research. We used Cak Ingkling -Indonesian hopscoth- as a context in line with PMRI -Indonesian version of Realistic Mathematics Education- approach. The research finding showed that the use of Cak Ingkling context can help students understand the definitions and types of quadrilaterals. Students have had the understanding that it has many quadrilateral shapes such as square, rectangle, rhombus, parallelogram, trapezoid, and kite.